连瀛洲与南洋大学 = Lien Ying Chow and Nanyang University - 曾馨莹 Chan, Sing Ying (2011)
南洋理工大学自 2009 年起把“南洋通道”的一段路改名为“连瀛洲通道”，除了纪念连瀛洲对南洋大学的贡献，也为他对新加坡的贡献表示肯定。连瀛洲参与了南洋大学的创办，是南大执委会的会员之一，后来还担任理事会会员长达 12 年。他不但捐钱资助创办南大，还亲自到校址勘查。不但如此，连瀛洲还四处奔波，到邻国发表言论，呼吁人民支持南大。当南大受到广大群众的质疑时，连瀛洲还得参与为南大辩解。为南大聘请第一位校长的重任也落在他的身上，当时连瀛洲甚至受托到美国聘请林语堂出任校长一职。后来林语堂与南大执委会闹翻，而连瀛洲也在林语堂离开南大后，从南大隐退，直到 1969 年在新加坡政府的要求下义无反顾地回返南大。虽然中间阔别南大 13 年，但连瀛洲仍然非常关心南大。回来后，连瀛洲主要担任守护者的角色，确保南大理事会不遇到大问题。这一期间，连瀛州也时常出钱资助南大，让南大能顺利办事。1980 年，南大前途茫然，新加坡政府曾致函连瀛洲商讨南大的未来去向，显示了连瀛洲对教育和南大的贡献已深受肯定，他们也非常重视他的意见。连瀛洲曾为保留南大声援，但南大最终仍逃不过合并的遭遇。南大虽然不复存在，但连瀛洲仍然以自己的能力守护着南大。即使连瀛洲在 2004 年与世长辞，他的后人为了续他与南大的情缘，近几年都以他创立的“连氏基金”与南洋理工大学发展合作计划。Since 2009, a stretch of Nanyang Drive was renamed Lien Ying Chow Drive, in commemoration of Dr Lien Ying Chow’s contribution to the development of Singapore and Nanyang University. Dr Lien was involved in the building of Nanyang University and was a member of the founding committee. He spent a lot of time and effort helping to the building of Nanyang University. Other than giving donations, he also went down to the site of construction and contributed to the decisions on the architecture. At times, Dr Lien had to go to the neighbouring countries to persuade the people to supporting Nanyang University. When the purpose of setting up Nanyang University was questioned, he had to help with the explanation. The job of searching for the first principal also fell unto Dr Lien, and he was entrusted with the task of persuading Dr Lin Yu Tang to take up the post. Although Dr Lien left the university after the disagreement Dr Lin had with the founding committee, he came back and joined the board of directors under the request of the Singapore government in 1969. Dr Lien was the guardian of the council, always making sure that the council faced no problems. During this period, he also made donations to ensure the university had enough funds in its daily operations. In 1980, the government had qualms about the future of Nanyang University and wrote to Dr Lien to seek his views. This goes to show that Dr Lien’s contribution to the Singapore education and Nanyang University was recognized, and that the government had a lot of trust in him. He proposed new ideas to save the university but the school was unable to escape from the merger. Even after Nanyang University ceased to exist, Dr Lien still in his way protected the people. After the demise of Dr Lien in 2004, his descendants used his “Lien Foundation” to work with Nanyang Technological University, to continue his support for the Nanyang spirit.